Civil Society and Pro-Democracy Social Movements: Troubled Relations Within Authoritarian Regimes? - Nasibov, Murad (Frontiers in Political Science, 2021)
This article tries to conceptually lay down the troubled relations between civil society and social movements within authoritarian regimes. This is done by, first, bringing clarity to the conceptual relationship between civil society and social movement and, then, applying it to the authoritarian context, still theoretically. Following the “hints” of the Eastern European intellectuals of the late 1970s and the 1980s and building on the appropriation of Durkheim’s differentiation between mechanical solidarity and organic solidarity, the article distinguishes two types of solidarity: associative solidarity and action and collective solidarity and action. Civil society is proposed to emerge on associative solidarities (and their actions), while social movements build on collective solidarities (and their actions). Furthermore, associative and collective actions are identified to be progressive and transgressive, respectively. Consequently, the proposed theoretical account is applied theoretically to the authoritarian context and several hypotheses are proposed on the relationship between civil society and pro-democracy movement within authoritarian regimes.